Elevated levels of maternal anti-tetanus toxin antibodies do not suppress the immune response to a Haemophilus influenzae type b polyribosylphosphate-tetanus toxoid conjugate vaccine - C. Panpitpat; U. Thisyakorn; T. Chotpitayasunondh; E. Fürer; J.U. Que; T. Hasler; S.J. Cryz Jr (Bulletin of the World Health Organization, 2000)
Reported are the effects of elevated levels of anti-tetanus antibodies on the safety and immune response to a Haemophilus influenzae type b polyribosylphosphate (PRP)-tetanus toxoid conjugate (PRP-T) vaccine. A group of Thai infants (n = 177) born to women immunized against tetanus during pregnancy were vaccinated with either a combined diphtheria-tetanus- pertussis (DTP) PRP-T vaccine or DTP and a PRP-conjugate vaccine using Neisseria meningitidis group B outer-membrane proteins as a carrier (PedVax HIB). Although most infants possessed high titres (>1 IU/ml) of anti-tetanus antibodies, the DTP-PRP-T combined vaccine engendered an excellent antibody response to all vaccine components. In both vaccine groups >98% of infants attained anti-PRP antibody titres >0.15 mg/ml. The geometric mean anti-PRP antibody titres were 5.41 mg/ml and 2.1 mg/ml for infants immunized with three doses of PRP-T versus two doses of PedVax HIB vaccines, respectively ( P< 0.005). Similarly, the proportion of infants who achieved titres >1 mg/ml was higher in the PRP-T group (87.8%) than in the group immunized with PedVax HIB (74.2%) (P = 0.036). A subgroup analysis showed that there was no significant difference in the anti-PRP antibody response for infants exhibiting either <1 IU of anti-tetanus antibody per millilitre or >1 IU/ml at baseline. These finding indicate that pre-existing anti-carrier antibody does not diminish the immune response to the PRP moiety. All infants possessed protective levels of anti-D and anti-T antibody levels after immunization.